Penerapan Metode Design Thinking dalam Perancangan UIUX Warehouse Management System - Manarul Hidayat; Frans Andrew Sinaga (Faktor Exacta, 2025)
Warehouse inventory management that is still done manually at PT. XYZ causes various problems such as stock discrepancies, slow delivery processes, and data loss. To overcome these problems, the company plans to develop a web-based warehouse management system or commonly called the Warehouse Management System. In the system design process, the implementation of User Interface (UI) and User Experience (UX) is an important aspect so that the application can be used effectively and efficiently by users. Figma is used as a tool in designing an interactive and collaborative interface. The Design Thinking approach is applied to explore user needs in depth through the stages of empathize, define, ideate, prototype, and test. System evaluation is carried out using the System Usability Scale (SUS) to ensure user comfort, effectiveness, and satisfaction with the prototype developed. The results of the usability test produced an Excellent score of 80.5. This proves that a well-designed UI/UX can bridge technology and user needs effectively.